Kepatuhan Pajak Badan : Peran Literasi, Kepercayaan dan Modernisasi Perpajakan Di Kota Denpasar - Ni Wayan Vinayanti; Ni Putu Budiadnyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Corporate tax compliance remains a persistent challenge in Indonesia despite ongoing efforts to improve tax administration through digitalization and policy reforms. In Denpasar City, fluctuations in corporate tax compliance indicate that structural improvements alone may not be sufficient to ensure consistent compliance behavior. This study aims to examine the effects of tax literacy and trust in tax authorities on corporate tax compliance, as well as to investigate the moderating role of tax administration modernization. A quantitative research design was employed using survey data collected from 99 corporate taxpayers registered at four Primary Tax Offices in Denpasar. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that tax literacy and trust in tax authorities have a positive and significant effect on corporate tax compliance. Furthermore, tax administration modernization strengthens the relationship between trust in tax authorities and corporate tax compliance, indicating that transparent and technology-based tax systems enhance the effectiveness of institutional trust. However, tax administration modernization does not moderate the relationship between tax literacy and compliance, suggesting that tax knowledge functions as an independent internal factor. The model explains 37.1% of the variance in corporate tax compliance, reflecting a moderate predictive capability. These findings highlight the importance of integrating taxpayer education with institutional trust-building and digital tax system development to promote sustainable corporate tax compliance.